Die OECD-PIAAC-Ergebnisse: Ein unerhörter Weckruf für Österreich! - Bösch, Valerie; Jellasitz, Robert; Schweighofer, Johannes (Wirtschaft und Gesellschaft, 2014)
Until recently, the OECD Survey of Adult skills (also called "PIAAC") did not cause any major reactions from stakeholders in Austria. This came somewhat as a surprise as one of the main results shows that approximately one million people in Austria are not able to fully participate in daily and working life due to lacking skills and competences. But maybe it is just the tremendeous volume of empirical results released that is difficult to digest in such a short time. This paper sheds light on the following aspects: How large is the group of very low achievers? Which competences do older people and persons with migrants background own? What can be said regarding informal learning at the work place? One of the main conclusions of the article refers to role of lifelong learning - though early education has long-term effects, the enhancement of skills and competences in the course of adult careers and work experiences is of crucial importance, too.